Immunogenic cell death: A new strategy to enhancing cancer immunotherapy - Lei Dou; Yu Fang; Huiyuan Yang; Guo Ai; Na Shen (Human Vaccines & Immunotherapeutics)
Immunogenic cell death (ICD) is a distinct type of stress-induced regulated cell death that can lead to adaptive immune responses and the establishment of immunological memory. ICD exhibits both similarities and differences when compared to apoptosis and other non-apoptotic forms of regulated cell death (RCD). The interplay between ICD-mediated immunosurveillance against cancer and the ability of cancer cells to evade ICD influences the host-tumor immunological interaction. Consequently, the restoration of ICD and the development of effective strategies to induce ICD have emerged as crucial considerations in the treatment of cancer within the context of immunotherapy. To enhance comprehension of ICD in the setting of cancer, this paper examines the interconnected responsive pathways associated with ICD, the corresponding biomarkers indicative of ICD, and the mechanisms through which tumors subvert ICD. Additionally, this review explores strategies for reinstating ICD and the therapeutic potential of harnessing ICD in cancer immunotherapy.